One of us : a novel - Chaon, Dan (Henry Holt and Company, 2025)
A playfully macabre and utterly thrilling tale about orphaned twins on the run from their murderous uncle who find refuge in a bizarre traveling carnival, from a master of literary horror It's 1915 and the world is transforming, but for thirteen-year-old Bolt and Eleanor-twins so close they can literally read each other's minds-life is falling apart. When their mother dies, they are forced to leave home under the care of a vicious con man who claims to be their long-lost uncle Charlie, the only kin they have left. During a late-night poker game, when one of his rages ends in murder, they decide to flee. Salvation arrives in the form of Mr. Jengling, founder of the Emporium of Wonders and father to its many members. He adopts Bolt and Eleanor, who travel by train across the vast, sometimes brutal American frontier with their new family, watching as the exhibitions spark amazement wherever they go. There's Minnie, the three-legged lady, and Dr. Chui, who stands over seven feet tall; Thistle Britches, the clown with no nose, and Rosalie, who can foretell the death of anyone she meets. After a lifetime of having only each other, Eleanor and Bolt are finally part of something bigger. But as Bolt falls in deeper with their new clan, he finds Eleanor pulling further away from him. And when Uncle Charlie picks up their trail, the twins find themselves facing a peril as strange as it is terrifying, one which will forever alter the trajectory of their lives. An ode to the misfits and the marginalized, One of Us is a riotous and singularly creepy celebration of the strange and the spectacular and of family in its many forms.